Detection of felipivirus in feces samples from cats in an animal shelter in Japan - JAFAR, Sheikhi Mohammad; MAUNG MAUNG KHIN, Shwe Thiri; TAKEMAE, Hitoshi; MIZUTANI, Tetsuya; FURUYA, Tetsuya (Journal of veterinary medical science, 2025)
Felipivirus is a feline picornavirus that was first discovered in fecal samples from stray cats in Hong Kong in 2012, and has been reported only in a few cases. We previously reported next-generation sequencing (NGS) analyses of fecal samples from 20 adult cats in an animal shelter in Tokyo, Japan, and now, in this study, report detection of felipivirus A2 from the same samples. Reverse transcription (RT)-PCR demonstrated the presence of the same virus in the 8 cats. Phylogenetic analyzes demonstrated a close relationship of the virus with some picornaviruses from wild animals such as raccoon dog and marmot. This study highlights the importance of surveillance of cats in animal shelters to detect viruses potentially originated from wild animals.